On the political dimension of political science – a few words about political dimension as the final judgment and reasoning - Rosicki, Remigiusz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
The subject of the text is the issue of the "political", which is defined as the nature and level of the final judgment and ultimate reasoning. The issues of this kind of the "political" has been attempted to distinguish in political sciences. The text focuses on: (1) the scientist as an agent for the final judgment and reasoning, (2) the subject of study of political science, (3) "theoretical strategies" in the science of politics. The latter problem has been discussed mainly on the example of Polish political science. Discussed were among others: (1) "the dilemma of scale", (2) limited operational capacity (methodological and theoretical), (3) aesthetic imagery of political life, (4) structural ignorance in the field of ontology, epistemology and methodology.

Przedmiotem tekstu jest problematyka „polityczności”, którą określono jako naturę i poziom ostatecznego rozstrzygnięcia i uzasadnienia. Problematykę tak rozumianej „polityczności” próbowano wskazać w naukach politycznych. W tekście skupiono się na: (1) naukowcu jako podmiotowi dokonującemu ostatecznego rozstrzygnięcia i uzasadnienia, (2) przedmiocie badań nauk o polityce, (3) „strategiach teoretycznych” w naukach o polityce Ostatni z wymienionych problemów został omówiony głównie na przykładzie polskiej politologii. Poruszono m.in. kwestie: (1) „dylematu skali”, (2) ograniczonych możliwości operacyjnych (metodologiczno-teoretycznych), (3) estetycznej metaforyki życia politycznego, (4) strukturalnej ignorancji w zakresie ontologii, epistemologii i metodologii.
Keywords: polityczność; the political; nauki polityczne; political sciences; teoria polityki; political theory; metodologia nauk politycznych; political science methodology; ostateczne uzasadnienie; ultimate reasoning; ostateczne rozstrzygnięcie; final judgment; strategie teoretyczne; theoretical strategies